Estimation of Chlorpyriphos in its Formulation (Paraban 20% EC) by Reversed-Phase HPLC - Deepti Joshi; N. K. Sand (E-Journal of Chemistry)
A method has been developed for estimation of active ingredient in chlorpyriphos formulation (Paraban 20% EC). The formulation was extracted in chloroform, dried and resuspended in acetonitrile. The cleanup was performed using C18 SPE cartridge. The active ingredient was estimated using 5 μm ODS-II column, mobile phase was acetonitrile: water (75:25 v/v) and detection at 229nm. The efficiency of clean up method was found to be 95% and minimum limit of detection < 2.5ng. The detector response was linear with in concentration range 2.5ng – 50ng at RSD 1.42%.